Theoretical Analysis of Rydberg and Autoionizing State Spectra of Antimony - 吕双飞 李若虹 贾凤东 李晓康 Jens Lassen 钟志萍 (Chinese physics letters, 2017)
We calculate the Rydberg and autoionization Rydberg spectra of antimony （Sb） from first principles by relativistic multichannel theory within the framework of multichannel quantum defect theory. Our calculation can be used to classify and assign the atomic states described in recently reported three Rydberg series and four autoionizing states. The perturbation effects on line intensity, variation and line profile are discussed. Assignments of the perturber states and autoionizing states are presented.